علم النفس الرياضي - زروقة، لطفي (My University, 2026)
الملخص : بالعربية : يعتبر علم النفس الرياضي هو أحد فروع علم النفس العام التي تستهدف دراسة سلوك الشخص الرياضي، ودراسة المؤثرات النفسية التي تؤثر على أدائه الرياضي، بالإضافة إلى دراسة العوامل التي تؤثر على النشاط الرياضي. فعلم النفس هو الدراسات العلمية للسلوك والعقل والتفكير والشخصية، ويمكن تعريفه بأنه: "الدراسة العلمية لسلوك الكائنات الحية، وخصوصا الإنسان، وذلك بهدف التوصل إلى فهم هذا السلوك وتفسيره والتنبؤ به والتحكم فيه". وكما أنه من العلوم المهمة حديثا ولم يتوسعوا فيه قديما، وهذا العلم لا يختصر على فرع واحد بل لديه عدة فروع وأقسام بالإضافة إلى ذلك فإنه من العلوم الممتعة مع أن دراسته قد لا تكون بالسهلة ويساعد هذا العلم في معرفة أنماط الشخصيات المختلفة.. يعتبر الهدف من دراسة علم النفس الرياضي محاولة لاكتشاف العوامل التي تؤثر في الشخصية الرياضية لتعزيز وتحسين الأداء الرياضي إلى الأفضل. Abstract:in English Sports psychology is a branch of general psychology that aims to study the behavior of athletes, the psychological influences that impact athletic performance, and the factors that influence athletic activity. Psychology is the scientific study of behavior, mind, thinking, and personality. It can be defined as: "The scientific study of the behavior of living organisms, especially humans, with the aim of understanding, explaining, predicting, and controlling this behavior." It is an important modern science that was not widely developed in the past. It is not limited to one branch, but rather encompasses several branches and divisions. Furthermore, it is an interesting science, although its study may not be easy. This science helps in understanding different personality types. The goal of studying sports psychology is to discover the factors that influence the athletic personality to enhance and improve athletic performance.
Keywords: 1) مفاهيم عامة حول علم النفس الرياضي; 2) نظريات علم النفس العام; 3) علاقة علم النفس العام بالرياضة